STRATEGI ALIANSI DALAM MENGHADAPI GLOBALISASI (STUDI PADA PERUSAHAAN KERAJINAN KULIT DI KABUPATEN MAGETAN) - Ahmadi, Herman (Widya Warta, 2013)
The problem faced by leather entrepreneurs in Magetan is concerned with the limitations of production capacity and design. So producers cannot meet buyers’ demand at a certain time. This problem can be overcome by making an alliance comprising several companies. This alternative is considered as the main solution on the problem.This alliance strategy model was proposed by Michael Yoshiro and Rosabeth Kanter. This alliance strategy can be of various forms which are, in fact, the basic forms of a marketing alliance including product or service alliance, promotional alliance, logistic alliance, and pricing collaborations.This reseacrh aims to give formulation strategy alternatives to be used by companies in making alliance. To obtain the exact strategy formulation requires the use of analysis tools, such as SWOT matrix, BCD matrix, and QSP matrix. It is started with an initial step of identifying both internal and external factors.The analysis of alliance strategy formulation on the leather companies by the use of SWOT, BCG, and QSPM recommend that the four strategies be done by each company with the priority order of application: (a) Strategic service alliance, (b) Strategic opportunity alliance, (c) Strategic pricing alliance, and (d) Strategic promotional alliance.